Marshall and Taney : statesmen of the law - Palmer, Ben W. (Benjamin Whipple), 1889- (University of Minnesota Press ; H. Milford : Oxford University Press, 1939)
Marshall and Taney was first published in 1939. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. The tides of social, political, and economic conflict will surge more violently about the Supreme Court in the future than they have in the past. Constantly larger numbers of the people are becoming aware of the tremendous power of the court as final interpreter of the constitution as a check upon Congress and the executive, and as guardian of individuals and minorities against governmental power. As a president of the American Bar Association has said, "Producers of potatoes in Maine, peanuts in Virginia, cotton in South Carolina, cane sugar in Louisiana, wheat in Kansas, corn in Iowa, peaches in Georgia, oranges in California, and thousands of small local enterprises everywhere are coming more and more to realize that their own bread and butter is seriously affected by the personnel of the Supreme Court. Since public opinion rules in America, the place that the court will occupy in the scheme of things will be determined by the thought and emotions of the people. Thought and emotion alike will, in turn, depend largely upon popular conceptions of the part played by the court. Those conceptions cannot be accurate without a knowledge of the functioning of the individual judge. We can better comprehend present and future judges if we understand why past ones acted officially as they did. This study contributes materially to that understanding. In the light of history and the law, Ben W. Palmer has made a clear and thought provoking analysis of the judicial function, indicated revolutionary changes in the law. In the sharply etched portraits of the two chief justices who molded American constitutional law in its formative stages, he has shown how and why these two men affect lawyer and laymen today."Law," says historian-lawyer Palmer, "like religion, government, art, science, receives its meaning and value, not because of what it has been or is, but because of what it accomplishes as an instrument for the benefit of humanity.""The judge's most essential and unavoidable function," thinks Dr. Palmer, "is the attempt to reconcile the contending principles of liberty and order. He stands between rule and discretion, the strict law and one tempered by time, circumstance, abstract justice, popular feelingall crying out for relaxation of the rule. He must stand between Shylock, with his shining knife of legal right, and the victim who calls to his compassion."